A strategic and tactical approach to global business ethics - Beer, Lawrence A. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
The inclusion of ethically driven elements into the strategic planning process of multinational corporations (MNCs) is an emerging consideration in the modern era of globalization. Firms pursuing cross-border activities in any capacity and to whatever degree or scale are increasingly coming into contact with differences in morally applied decision making that affects their operational success and sustainability. The choices made require the use of clear and unambiguous codes of conduct for embedded managers abroad. The implementation of a properly administered code, coupled with a program of corporate social responsibility (CSR), can add value to a company, while its misapplication or exclusion can diminish value.
1. Ethics in commerce -- 2. Ethics and the strategic determination -- 3. Ethical value development -- 4. Ethics unabridged -- 5. Time for a change? -- 6. A universal code template -- 7. Global ethical strategies and conclusions -- Notes -- References -- Index.
Includes bibliographical references (pages 301-308) and index.
Title from PDF title page (viewed on January 27, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business ethics; International business enterprises -- Moral and ethical aspects; Social responsibility of business; code of conduct; corporate social responsibility (CSR); ethical dilemma; ethics; global labor; globalization; multinational corporation (MNC); repressive governments; strategy; Electronic books